Boosting KFC's Indonesia Market Dominance via SWOT (Strengths, Opportunities, Weaknesses, Threats) and STP (Segmentation, Targeting, Positioning) - Aries Sundoro (Tinta Emas Institute, 2023)
The surge in fast food consumption has transformed Indonesian society into fast food enthusiasts, with one of the most popular products being KFC (Kentucky Fried Chicken). This restaurant offers dishes such as fried chicken, hamburgers, and other fast-food items, along with a variety of ready-to-eat beverages. The consumption of KFC in Indonesia has witnessed rapid growth, particularly in urban areas. As fast-food consumption rises, attention has turned to the factors and strategies employed by the company. For this reason, this research aims to explore the marketing strategies applied by KFC, using SWOT analysis, which includes strengths, weaknesses, opportunities, and threats, along with STP analysis (Segmenting, Targeting, Positioning), which have made it a market leader in Indonesia. This study employs a descriptive quantitative method with data gathered from secondary sources, online resources, and relevant literature pertaining to Kentucky Fried Chicken. The results of this research reveal that Kentucky Fried Chicken conducts marketing activities by segmenting its customers based on demographic, geographic, psychographic, and behavioral factors. Their products are targeted at a diverse range of age groups, from children to adults, excluding toddlers. Kentucky Fried Chicken positions itself as a superior and high-quality fast-food producer with affordable prices and a variety of Indonesian culinary flavors.